EDUCATIONAL APPROACHES OF SCHOOL PHYSICAL EDUCATION: PANORAMA OF THE PUBLIC SCHOOL. (Fiep Bulletin - online, 2014)
This study aims to identify the main pedagogical approaches used by teachers to plan / teach the physical education classes in the final years of primary education in the public schools of Erechim, RS. It has a quantitative and qualitative character and sought to collect data that allowed a mapping of how physical education is being taught in schools of this city. It was interviewed 100% of public school teachers in urban areas and working with physical education in the final years of primary school. The data indicate that we are still developing a physical education with strong traditional tendencies within a mechanistic and technicist perspective. Still, the refreshing approach used most frequently is the psychomotor and the PCN, s were only used for about 16% of teachers who use some form of refreshing approach. We realize that the school PE pedagogical intentionality is in need of a revival, a kind of recycling and (re) problematization in schools where the data of this study was collected.
Keywords: Professional formation; Continuing formation; Teaching methodology